2015
DOI: 10.1589/jpts.27.1087
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the coefficient of variation of stride time of the elderly without falling history: a prospective study

Abstract: [Purpose] The purpose of this study was to investigate the factors affecting the coefficient of variation (CV) of stride time in an exercise intervention for the elderly without falling history. [Subjects and Methods] The subjects were 42 elderly women who had participated in a care prevention program for 12 weeks. Stride time CV, motor function, movement ability, balance, Modified Falls Efficacy Scale (MFES) score, and Life-space Assessment (LSA) score before and after the intervention were examined for signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 14 publications
2
21
0
1
Order By: Relevance
“…The significant interaction found in the stride time may have occurred due to the high variability between individuals (i.e., large standard deviations), although the average change was low. Indeed, a similar stride time CV (2.2±1.3%) was reported in a previous study for healthy elderly 29 . In addition, the spatiotemporal gait parameters presented lower mean variability (1-4%) in comparison to the study performed by Hollman and colleagues 28 for older women (3-8%), but similar to previous that included young and older adults 30 .…”
Section: Discussionsupporting
confidence: 89%
“…The significant interaction found in the stride time may have occurred due to the high variability between individuals (i.e., large standard deviations), although the average change was low. Indeed, a similar stride time CV (2.2±1.3%) was reported in a previous study for healthy elderly 29 . In addition, the spatiotemporal gait parameters presented lower mean variability (1-4%) in comparison to the study performed by Hollman and colleagues 28 for older women (3-8%), but similar to previous that included young and older adults 30 .…”
Section: Discussionsupporting
confidence: 89%
“…The ranges of the categories selected for the stride interval CV were also chosen in accordance with CVs reported in other studies about stride interval variability in elders with/without falling history [15,[26][27][28]. These studies shown similar results, with healthy elderly population within the range of 1.7 to 2.6% for the stride interval CV [27] and those with a history of fall within 3.0 ± 2.8% [28].…”
Section: Descriptive Statistical Analysismentioning
confidence: 85%
“…Third, this study revealed the correlation between walking speed and acceleration variability of the head, lumbar, and lower extremities in young people. Movement variability is associated with the ability to walk in elderly people 7 ) . Thus, further studies are required to determine the effects of age-related alternations in the acceleration variability, particularly in the ML direction, through simultaneous evaluations of the head, lumbar, and lower extremities of elderly people.…”
Section: Discussionmentioning
confidence: 99%
“…Increased in movement variability during walking is associated with a reduction in the coordination required for efficient walking control 6 ) . Matsuda et al 7 ) reported that the stride time variability is associated with muscle strength, flexibility and balance ability in elderly people. Analysis of movement variability during walking may enhance the understanding of motor control and enable the prediction of an individual’s ability to walk.…”
Section: Introductionmentioning
confidence: 99%